(untitled) (Research, Society and Development, 2021)
The present work conceptually debates education 4.0 in the scope of military education. It is known that the military activity has and uses several cutting-edge technologies, which demand accurate knowledge for their application. Thus, we cannot conceive the evolution of education 4.0 in the civilian environment without extending this knowledge to the military environment. In addition, the incorporation of procedures for the generation, maintenance and perpetuation of knowledge is fundamental so that it is not restricted to a few, reaching the various operational levels of the Land Force. It is in this fertile terrain that Knowledge Management emerges as a repository and a capillary of information.